Development of Slovak-Serbian cultural and scientific ties: Matica slovenská’s cooperation with Matica srpska and the Archives of Vojvodina - Gašper, Marijan (Napredak, 2026)
The text provides an overview of specific events and activities organized by or attended by the Matica slovenská, in efforts to strengthen Slovak-Serbian ties, especially those between the Matica srpska and Matica slovenská. In that context, the text lists the congresses organized by the two institutions, which represent a platform for cooperation of the two Maticas and the Slavic peoples’ institutions, which developed significant cooperation during their existence in the field of the two peoples’ history research and culture. The text also features significant anniversaries of both Maticas, as well as planning joint publishing projects and joint participation in cultural events.